Quilt big : bigger blocks for faster finishes - Flendt, Jemima (Blue Ash, Ohio : The Quilting Company, 2018)
Big, bold, impressive designs that sew together quickly and easily! Approaching quilting in a big way, Quilt Big takes the inherent beauty found in single block patterns and creates big, bold quilts, quickly and easily. Whether you're simply short on time or intimidated by complex quilts, Quilt Big will show you how super-sizing your blocks make for faster finishes and so much more. In this block book and design resource, you'll find: 22 BIG blocks to show off your favorite fabrics in fantastic ways. Step-by-step guide to scaling traditional blocks to oversized designs. 17 quilt designs featuring bold, super-sized blocks. Plus, these 15", 18", and 24" blocks are interchangeable for one-of-a-kind finished projects! No CD required! Block patterns have been designed in a way that no specially sized templates are needed. If you're new to quilting, there's no better way to learn than on a grand scale. And, for the experienced quilter, large block pieces are a fabric-friendly way to feature your favorite designer collections. Super-size your love of quilting with Quilt Big!
Quilting basics -- Upsizing quilts and quilt blocks -- Quilt blocks -- Quilts and home decor projects -- Quilt backings.
Includes index.
107432
Keywords: Quilting -- Patterns; Patchwork -- Patterns; DESIGN -- Textile & Costume; Nonfiction; Patterns